Association Between Social Participation and 3‐Year Change in Instrumental Activities of Daily Living in Community‐Dwelling Elderly Adults. Issue 1 (27th September 2016) - Tomioka, Kimiko; Kurumatani, Norio; Hosoi, Hiroshi
Abstract : Objectives: To investigate whether social participation (SP) in older adults is associated with ability to perform instrumental activities of daily living (IADLs). Design: Prospective cohort study. Setting: Two local municipalities of Nara, Japan. Participants: Individuals aged 65 to 96 (n = 2, 774 male, n = 3, 586 female) free of IADL disability at baseline. Measurements: SP and IADLs were assessed using self‐administered questionnaires. SP was categorized into five types and assessed using the number and type of social activities. IADLs were evaluated using the Tokyo Metropolitan Institute of Gerontology Index of Competence. Logistic regression analysis stratified according to sex was used to examine change in IADLs according to SP, with nonparticipation as a reference. Results: During the 3‐year follow‐up, 13.6% of men and 9.0% of women reported IADL decline. After adjusting for age, family structure, body mass index, pension, occupation, medical treatment, self‐rated health, drinking, smoking, depression, cognitive function, and activities of daily living, participation in various social activities was inversely associated with change in IADLs in women but not men. Participation in the following types of social activities had significant inverse associations with IADL disability: hobby clubs (odds ratio (OR) = 0.68, 95% confidence interval (CI) = 0.49–0.94) for men and local events (OR = 0.68, 95% CI = 0.48–0.95), hobby clubs (OR = 0.53, 95% CI = 0.36–0.79), senior citizen clubs (OR = 0.74, 95% CI = 0.56–0.97), and volunteer groups (OR = 0.56, 95% CI = 0.32–0.99) for women. Conclusion: Participation in a variety of different types of social activities was associated with change in IADLs over the 3 years of this study in women, and participation in hobby clubs was associated with change in IADLs in men and women. Recommending that community‐dwelling elderly adults participate in social activities appropriate for their sex may promote successful aging.